The Application of Practical Clothing Design Method in the Teaching of Clothing Specialty. (4th August 2022) - Li, Miao; Fu, Rong
Abstract : To improve the teaching practice effect of clothing major, this study applies the practical clothing design method to the teaching of clothing major to analyze the digital clothing design and establishes a convex quadratic conic programming model for a class of force optimization problems. Then, this study transforms the optimality condition of the problem into a new projection equation system, constructs a suitable constant coefficient matrix according to the characteristics of the equation system, and obtains an equivalent linear equation system. In addition, this study proposes a full Newton step projection algorithm to directly solve the convex quadratic conic programming. Through the results of the experimental research, it can be seen that the practical clothing design method has a good application in the teaching of clothing majors, and it can be applied in the practice of clothing teaching.